MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU SEKOLAH DASAR - Rusmalawati, Rusmalawati; Rizki, Sari; Mulyadi, Said (Universitas Indraprasta PGRI, 2024)
This research aims to analyze the planning, organizing, implementation, and supervision carried out by elementary school principals in Central Aceh Regency to improve teacher performance. The study uses a descriptive qualitative approach, with data collected through interviews, observation, and documentation. The subjects were determined using the Cluster Random Sampling technique, where several clusters were formed from selected individuals within the population. The results of this study indicate that the planning carried out by the principal to improve teacher performance includes: 1) Continuous Professional Development (CPD), 2) Mentoring and Monitoring, 3) Support and Guidance, 4) Building a supportive work environment, 5) Activating learning communities, 6) Performance structuring, 7) Feedback, 8) Observation. The organization carried out by the principal to enhance teacher performance involves: 1) Teachers' academic competence and qualifications, 2) Years of teaching experience, 3) Relevant certification and licensing, 4) Pedagogical skills, 5) Mastery of teaching and classroom management, 6) School needs analysis, 7) Organizational culture alignment. The principal's implementation efforts to improve teacher performance include actively monitoring and ensuring the teachers' ability to plan and prepare lessons, mastery of the subject matter, teaching strategies, classroom management, and student evaluation. Supervision is conducted through: 1) Classroom observation, 2) Spontaneous classroom visits, 3) Peer evaluation, and 4) Student evaluation.